Outbreak investigation of acute diarrheal disease in Palitana urban, Gujarat - Koria, Bharti; Boricha, B. P.; Munsi, Hirava; Sarvaiya, Jatin (International Journal Of Community Medicine And Public Health, 2017)
Background: Clustering of diarrhoea and vomiting cases were reported in Palitana urban on 22 December 2014. Rapid response team was sent from government medical college, Bhavnagar to control the epidemic. Methods: A cross sectional study was conducted in Palitana urban for acute diarrheal disease epidemic investigation. Secondary data obtained from health staff and analysed to have clear picture of epidemic. Necessary actions were taken to control it. Results: Total 390 cases were reported. Out of them 21-30 adult age group was more affected as compared to other age groups. Attack rate of diarrheal disease was more in male population (85.61%) as compared to female population (40.99%).Over all attack rate was 64.19%. Conclusions: It was an acute diarrheal disease outbreak due to mixing of drinking water with polluted water.